Pengaruh Lingkungan Kerja Dan Kedisiplinan Kerja Terhadap Kinerja Karyawan Melalui Kepuasan Kerja - Rihva Dwi Andanni; Robby Dharma; Omia Crefioza (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of work environment and work discipline on employee performance with job satisfaction as an intervening variable at CV. Citra Dragon Teknik. This research was motivated by the company’s failure to consistently achieve production targets, indicating problems in employee performance. The study employed a quantitative method with a survey approach. The population consisted of all employees of CV. Citra Dragon Teknik, using a saturated sampling technique. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results indicate that work environment and work discipline have a positive and significant effect on job satisfaction. Work environment, work discipline, and job satisfaction also have a positive and significant effect on employee performance. Job satisfaction is proven to mediate the relationship between work environment and work discipline on employee performance. These findings highlight the importance of creating a conducive work environment and implementing consistent work discipline to improve employee satisfaction and performance.